LINGUOCULTURAL CHARACTERISTICS OF THE LEXEME 'GUL' (FLOWER) IN UZBEK LITERATURE - Elmirzaeva Zarina Obidin qizi (Bright Mind Publishing, 2025)
This article explores the linguocultural characteristics of the lexeme “gul” (“flower”) in Uzbek literature. It analyzes its semantic, metaphorical, and aesthetic functions as represented in folk oral creativity, classical poetry, and modern literature. Through this analysis, it reveals how national mentality, value systems, and aesthetic views are reflected. The study also provides examples of idiomatic expressions and poetic metaphors based on the lexeme “gul” and discusses their linguocultural features.
Keywords: Flower, linguoculture, image, literary representation, national worldview, semantics, metaphor.